A Patient With Multiple Sclerosis and Coexisting Moyamoya Disease: Why and How - Si, Xiaoli; Li, Lingfei; Fang, Yuanjian; Yan, Yaping; Pu, Jiali (Frontiers in Neurology, 2020)
Introduction: Multiple sclerosis (MS) and moyamoya (MM) are two separate diseases that rarely coexists. A special case with the two diseases coexisting was reported herein and previously published articles were reviewed to investigate the clinical manifestations, management, outcomes and underlying pathogenesis. Patient concerns: A 42-year-old male presented with gradually right limbs weakness and slow response for 3 months. However, these symptoms abruptly progressed during his hospital stay. Diagnosis: This patient was diagnosed coexisting MS and MM finally. The diagnosis of MS was made according to McDonald criteria of multiple lesions and multiple time episode. Meanwhile, cerebral angiography indicated the diagnosis of MM. Interventions: This patient was treated with methylprednisolone and antiplatelet drug, and received bilateral superficial temporal artery bypass surgery for the occulted artery. Outcomes: This patient’s right limbs recovered to 4/5 grade muscle strength after one month follow-up after hospital discharge and his speech function improved after three months after hospital discharge. Conclusion: We reported a rare scenario in a patient with the coexistence of MS and MM. We suspect MS might induce immune response that play a role in the pathogenesis of MM, while MM might accelerate the demyelination of MS. However, pathogenesis and therapeutics of MM and MS co-exit need further investigation.